Corrigendum to “Neuromuscular synapse degeneration without muscle function loss in the diaphragm of a murine model for Huntington's Disease" - Valadão, Priscila A.C.; Gomes, Matheus P.S.M.; Aragão, Bárbara C.; Rodrigues, Hermann A.; Andrade, Jéssica N.; Garcias, Rubens; Joviano-Santos, Julliane V.; Luiz, Murilo A.; Camargo, Wallace L.; Naves, Lígia A.; Kushmerick, Christopher; Cavalcante, Walter L.G.; et al. (Elsevier, 2018)
The authors regret that the trace in Fig. 6H was the same as from Fig. 6I. We have inserted the correct trace in Fig. 6H. The authors would like to apologise for any inconvenience caused.